Existing Conditions of Tourism Destinations in Indonesia - Anisa Putri Kusumaningrum; Kumba Digdowiseiso (Budapest International Research and Critics University, 2022)
The tourism industry sector is an important contributor to the economy and one of the factories, especially those that create foreign currency that is very necessary in the national economy. The objectives of the study are: (1) Identifying Potential Tourism Objects, (2) Mapping the Spread of Potential Tourist Objects, (3) Identifying existing tourist objects and destinations. Information analysis was tried qualitatively- interpretively looking at the progress of tourism and the incidence of the tourism situation in this endemic era of Covid-19 in various tourism regions in Indonesia. The results of the analysis of library or literature prove that the ruler has shared special wisdom in the tourism zone upgrade chart, and various tourism destination areas have also practiced strategies and programs that are able to adjust to the situation that is said to be a new normal period, and there is a change in tourist attitudes.